SISTEM INFORMASI LOGISTIK KARGO MENGGUNAKAN METODE AGILE (EXTREME PROGRAMMING) DI PT. XYZ - Hendriana, Hendra; Rohayati, Tuti; Mulyana, Dadan (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The development of the logistics industry requires an integrated information system to facilitate the management of goods delivery. PT. XYZ, as a cargo logistics service company, needs a digital solution to minimize recording errors, accelerate tracking, and improve customer service. This study aims to develop a cargo logistics information system using the Extreme Programming (XP) methodology, which emphasizes flexibility and rapid development through the stages of planning, design, coding, and testing. The system was developed using the PHP programming language with the Laravel framework and a MySQL database, and was tested using Blackbox Testing to ensure its functionality. The implementation results show that the system is capable of managing waybills, tariffs, manifests, and reporting in an integrated manner, accelerating the input and tracking processes, and reducing potential data errors, thereby supporting the company’s operational needs.